Rate of decline in residual kidney function pre and post peritoneal dialysis initiation: A post hoc analysis of the IDEAL study - Ethier, Isabelle; Cho, Yeoungjee; Hawley, Carmel; Pascoe, Elaine M.; Viecelli, Andrea K.; Campbell, Scott B.; van Eps, Carolyn; Isbel, Nicole M.; Cooper, Bruce A.; Harris, David C.; Pollock, Carol A.; Wong, Muh Geot; et al. (PloS one, 2020)
Residual kidney function (RKF) is associated with improved survival and quality of life in dialysis patients. Previous studies have suggested that initiation of peritoneal dialysis (PD) may slow RKF decline compared to the pre-dialysis period. We sought to evaluate the association between PD initiation and RKF decline in the Initiating Dialysis Early And Late (IDEAL) trial. In this post hoc analysis of the IDEAL randomized controlled trial, PD participants were included if results from 24-hour urine collections had been recorded within 30 days of dialysis initiation, and at least one value pre- and one value post-dialysis commencement were available. The primary outcome was slope of RKF decline, calculated as mean of urinary creatinine and urea clearances. Secondary outcomes included slope of urine volume decline and time from PD initiation to anuria. The study included 151 participants (79 early start, 72 late start). The slope of RKF decline was slower after PD initiation (-2.69±0.18mL/min/1.73m2/yr) compared to before PD (-4.09±0.33mL/min/1.73m2/yr; change in slope +1.19 mL/min/1.73m2/yr, 95%CI 0.48-1.90, p<0.001). In contrast, urine volume decline was faster after PD commencement (-0.74±0.05 L/yr) compared to beforehand (-0.57±0.06L/yr; change in slope -0.18L/yr, 95%CI -0.34--0.01, p = 0.04). No differences were observed between the early- and late-start groups with respect to RKF decline, urine volume decline or time to anuria. Initiation of PD was associated with a slower decline of RKF compared to the pre-dialysis period.